2020
DOI: 10.2147/jpr.s244372
|View full text |Cite
|
Sign up to set email alerts
|

<p>Blue Mussel (<em>Mytilus edulis</em>) Water Extract Ameliorates Inflammatory Responses and Oxidative Stress on Osteoarthritis in Obese Rats</p>

Abstract: Purpose: To investigate the effects of Mytilus edulis water extract (MWE) on an anterior cruciate ligament transection and a partial medial meniscectomy surgery to induced osteoarthritis (OA) with the high-fat diet (HFD)-induced obese rats. Methods: The male Sprague-Dawley rats were fed with HFD for 4 weeks before surgery. The OA rats were orally administered with MWE (108.5, 217.0, and 542.5 mg/kg) for 6 weeks. Results: The administration of MWE affected weight loss, triglycerides content, and total cholester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…(2020) found that a water extract of blue mussels decreased LPO and reduced inflammation in rats with osteoarthritis. However, the levels of the SOD enzyme were not correlated with the amount of P. canaliculus in the diet, which is not consistent with the literature (Chang et al., 2020; Freitas et al., 2020), as animals were not receiving any toxins that would trigger the production of oxygen species. As a result, SOD was not increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2020) found that a water extract of blue mussels decreased LPO and reduced inflammation in rats with osteoarthritis. However, the levels of the SOD enzyme were not correlated with the amount of P. canaliculus in the diet, which is not consistent with the literature (Chang et al., 2020; Freitas et al., 2020), as animals were not receiving any toxins that would trigger the production of oxygen species. As a result, SOD was not increased.…”
Section: Discussionmentioning
confidence: 99%
“…It is considered a significant food source rich in various nutrients such as protein, lipids, and carbohydrates (Santhanam, 2014) and can have a therapeutic effect in treating several diseases. Recently, several studies have focused on the value of marine life and its use as a potent food source (Sargent, 1997), as well as some of its biologically active ingredients that could be used as anticancer agents (Aldairi et al., 2018; Khurshid & Pye, 2018), cardioprotective agents (Matanjun et al., 2010), and antioxidant source (Chang et al., 2020). In this regard, molluscs are the most noticeable group of marine organisms due to their associated health benefits (Khan & Liu, 2019); therefore, its daily consumption would be beneficial in preventing many illnesses (Khan & Liu, 2019; Nongmaithem et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies of abnormal blood lipid metabolism and OA have found that elevated serum triglycerides are risk factors for the progression of OA. 81 Davies-Tuck et al reported that triglycerides are associated with the prevalence of BMLs in asymptomatic middle-aged women for more than two years. The results of this study provide a basis for the hypothesis that vascular pathological changes are involved in the progression of OA.…”
Section: Obesity-related Biological Processes and Oamentioning
confidence: 99%
“…OA can be induced by direct damage of knee joint cartilage by application of monosodium iodoacetate (MIA model) or other harmful agents. 71 , 72 The other models are based on creating knee instability by destabilization of the medial meniscus (DMM model) through transsection of the medial anterior meniscotibial ligament (MAMTL) which fixes the medial meniscus at the tibial plateau 73 or by transsection of the medial collateral ligament (MCL) together with removal of the medial meniscus (MCL-MMx model), transsection of the medial meniscus (medial meniscus transection: MMT model) 71 , 73 , 74 , of the ACL (ACLT model) 75 , 76 or combinations of them. 76 Novel models based on joint cartilage overloading by high impact or cyclic overloading (inducing non-invasively posttraumatic joint injury leading to posttraumatic OA [PTOA]) have also been proposed.…”
Section: In Vitro and In Vivo Disease Models For Elucidation Of Oa Thmentioning
confidence: 99%